2017
DOI: 10.1111/aogs.13074
|View full text |Cite
|
Sign up to set email alerts
|

New guidelines for screening, diagnosing, and treating gestational diabetes – evaluation of maternal and neonatal outcomes in Finland from 2006 to 2012

Abstract: In conclusion, glucose tolerance tests were performed twice as often as a result of the implementation of the national GDM guidelines, but this comprehensive screening practice did not improve pregnancy and neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…Before 2008, GDM diagnosis was made if at least one of the following plasma glucose levels was observed in the 75-g oral glucose tolerance test: fasting value ⩾5.1 mmol/L, 1 h value ⩾10.0 mmol/L, or 2 h value ⩾8.6 mmol/L. 12 The oral glucose tolerance test was recommended at gestational weeks 24-28 for pregnant women with a pre-pregnancy body mass index (BMI) ⩾25 kg/m 2 , presence of glycosuria, age >40 years, fetal macrosomia in current or previous pregnancy, GDM in previous pregnancy, or a first-degree family history of diabetes. 12 Since 2008, GDM has been diagnosed when with fasting plasma glucose value ⩾5.3 mmol/L, the 1 h value ⩾10.0 mmol/L, or the 2 h value ⩾8.6 mmol/l.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before 2008, GDM diagnosis was made if at least one of the following plasma glucose levels was observed in the 75-g oral glucose tolerance test: fasting value ⩾5.1 mmol/L, 1 h value ⩾10.0 mmol/L, or 2 h value ⩾8.6 mmol/L. 12 The oral glucose tolerance test was recommended at gestational weeks 24-28 for pregnant women with a pre-pregnancy body mass index (BMI) ⩾25 kg/m 2 , presence of glycosuria, age >40 years, fetal macrosomia in current or previous pregnancy, GDM in previous pregnancy, or a first-degree family history of diabetes. 12 Since 2008, GDM has been diagnosed when with fasting plasma glucose value ⩾5.3 mmol/L, the 1 h value ⩾10.0 mmol/L, or the 2 h value ⩾8.6 mmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…12 The oral glucose tolerance test was recommended at gestational weeks 24-28 for pregnant women with a pre-pregnancy body mass index (BMI) ⩾25 kg/m 2 , presence of glycosuria, age >40 years, fetal macrosomia in current or previous pregnancy, GDM in previous pregnancy, or a first-degree family history of diabetes. 12 Since 2008, GDM has been diagnosed when with fasting plasma glucose value ⩾5.3 mmol/L, the 1 h value ⩾10.0 mmol/L, or the 2 h value ⩾8.6 mmol/l. 24 The oral glucose tolerance test is recommended for all pregnant women, except those at low risk (nulliparous women <25 years old with normal BMI and no family history of type 2 diabetes, and parous women <40 years old with normal BMI and no GDM or macrosomic child in a previous pregnancy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of comprehensive screening has resulted in an increase in the incidence of GDM during recent years. 22 , 23 The screening frequency has increased from 51.4% in 2009–12 to 66.0% in 2018, and the prevalence of GDM increased from 11.3% to 21.3%, respectively. 24 Thus, some women with GDM remained undiagnosed when our study was conducted.…”
Section: What Are the Main Strengths And Weaknesses?mentioning
confidence: 99%
“…Some previous studies showed that gestational diabetes mellitus (GDM) was not signi cantly correlated with NA [17,23]. While recent research has demonstrated that, a 1% increase (a unit increase) in HbA1c was observed to be associated with 2.99 times higher odds of NA [95%CI 1.31, 3.85] [24].…”
Section: Introductionmentioning
confidence: 99%